COMPARATIVE ANALYSIS OF THE RESULTS OF USING PEPTIDES AND CITICOLINE AT DIFFERENT STAGES OF RETINITIS PIGMENTOSA - Mammadzada, A.N.; Kasimov, E.M.; Aliyeva, N.I.; Orujova, S.N. (World of Medicine and Biology, 2024)
Retinitis pigmentosa is a severe hereditary pathology in ophthalmology and represents a medical and social problem. The purpose of the study was to establish hemodynamic parameters in the vessels of the eye and electrophysiological parameters of the retina in patients with different stages of retinitis pigmentosa before and after the use of peptides and citicoline and to conduct a comparative analysis of the results. 56 patients (112 eyes) diagnosed with retinitis pigmentosa aged 25–44 were examined. Electroretinography and colour Doppler mapping of the central retinal artery and short posterior ciliary arteries were performed. The patients were treated with endonasal electrophoresis with Retinalamin and Omk1 instillation. All patients showed a statistically significant decrease in hemodynamic parameters and electroretinography parameters. After treatment, hemodynamic and electroretinography parameters increase, and the effect is longer in the subgroup with combined therapy.